Synthesis of Isothiocyanates: An Update - Eschliman, Kayla; Bossmann, Stefan H. (Synthesis, 2019)
Isothiocyanates (ICTs) are a group of molecules that can be used for many different purposes, they exhibit anticancer, antimicrobial, antibiotic, and anti-inflammatory properties. The synthesis of isothiocyanates has been a focus of many researchers for nearly the past 100 years. One of the most common synthetic methods is to form a dithiocarbamate salt, either as the first step or in situ, and then treat the salt with a desulfurization agent to reach the isothiocyanate. There are many different desulfurization agents available. Among these, there are eleven in particular that will be discussed in this short review, namely thiophosgene, lead nitrate, ethyl chloroformate, hydrogen peroxide, triphosgene, iodine, cobalt, copper, sodium persulfate, claycop, and tosyl chloride. There are four additional particular methodologies that stand out from the literature available on this topic that will be covered, namely the production of isothiocyanates from hydroximoyl chlorides, via elemental sulfur, microwave-assisted synthesis, and through the tandem Staudinger/aza-Wittig reactions.1 Introduction1.1 Metabolism of Glucosinolates2 Synthesis of Isothiocyanates2.1 Isothiocyanates from the Decomposition of Dithiocarbamate Salts2.2 Isothiocyanates from Hydroximoyl Chlorides2.3 Isothiocyanates Produced via Elemental Sulfur2.4 Microwave-Assisted Synthesis of Isothiocyanates2.5 Isothiocyanates via the Tandem Staudinger/aza-Wittig Reactions3 Conclusion
Keywords: isothiocyanate; green alternatives to thiophosgene; sulfur; tandem Staudinger/aza-Wittig reactions